The Information on Islamic Education Marketing Services at MA Pondok Pesantren Ash-Shiddiqiyah Rantau Kasih Musi Banyuasin - A Sibron; Zainal Berlian; Ahmad Zainuri (The Future of Education Journal, 2024)
Islamic education at Islamic boarding schools plays a crucial role in shaping the character, morality, and spirituality of students. MA Pondok Pesantren Ash-shiddiqiyah Rantau Kasih MUBA combines a national curriculum with Islamic values to produce graduates who excel academically and possess commendable morals. This study analyzes the marketing strategies employed by the institution to attract prospective students and enhance its reputation amidst growing competition in the education sector. By utilizing digital platforms, social media, and partnerships with Islamic organizations, the pesantren has successfully increased its visibility and appeal. However, challenges such as limited financial and human resources and resistance to change remain. Addressing these challenges through training, partnerships, and innovation in digital marketing will enable the pesantren to sustain its growth and contribute to developing high-quality Islamic education in the modern era.